LOS ASTILLEROS Y LA INDUSTRIA MARITIMA EN EL PACIFICO AMERICANO: SIGLOS XVI A XIX - León Sáenz, Jorge (2009)
This report is part of a larger study funded by the University of Costa Rica on maritime commerce and navigation between Central America and Perú between 1700 and 1850. The focus is on the shipbuilding industry in the Pacific coast of Central America from the XVI to early XIX centuries. The main shipyards are identified as well as the sources of the different materials required for shipbuilding.  Shipbuilding was an important regional industry in the period. The existence of good quality woods and of a knowledge of shipbuilding techniques -empirically based and passed from on generation to another - were the essential elements for setting up a shipbuilding industry. Some problems requiring further research are presented. Annexs dealing with a description of all identified shipyards and of ships built in Central America complete the paper.